Periprosthetic joint infection associated with Mycoplasma hominis after transurethral instrumentation in an immunocompetent patient. Unusual or underestimated? A case report and review of the literature. (May 2019) - Rieber, Heime; Frontzek, Andre; Fischer, Martin
Highlights: PJI caused by Mycoplasma hominis is rare in immunocompetent patients. Generally, surgeons are not aware of risk factors. The laboratory has to carry out suitable procedures for its detection. The patient was successfully treated with levofloxacin and doxycycline. The prosthesis was retained. Abstract: Judging by the small number of published cases, periprosthetic joint infections (PJI) caused by Mycoplasma species are regarded as unusual. This is not surprising as special growth conditions are necessary for diagnosis and therefore the laboratory must be informed of any clinical suspicion. However, surgeons are generally not aware of the risk factors associated with certain microorganisms causing an infection. Our laboratory therefore decided to adopt a new strategy: first, to address specific questions concerning the medical history of the patient and second, to make diagnosis of rare and fastidious microorganisms part of routine investigation, even if detailed information is not available.